Reading anxiety and reading comprehension performance of ESL learners / Nurul Azani Samsuddin - Samsuddin, Nurul Azani (2013)
It has been negatively associated between the anxiety and students' performance as it symbolized the fear of learning second/foreign language that affected the students in acquiring the new language. This study began with the assertion that there was a relationship between reading anxiety and reading comprehension performance and the reading anxiety was associated to language anxiety but distinguish in certain part. This research aims to explore the relationship between the variables consist of the LA (Language Anxiety), RA (Reading Anxiety) and the reading comprehension performance. The study was conducted to 80 Diploma TESL (Teaching English as a Second Language) students in UNISZA (Universiti Sultan Zainal Abidin). The instrumentations included were the multiple-choice reading tests and survey questionnaire which consisted of three main sections, the demographic, the English Language Classroom Anxiety Scale (ELCAS) and the English Language Reading Anxiety Scale (ELRAS). Descriptive statistics of frequencies and correlational analysis were done to analyze the data and the result was interpreted. The results signified that the level of RA and LA among the respondents were high despite the fact that they also scored excellent result in the reading comprehension test. There were also relationships among the variables. This study was concluded by elaborating the factors that influence the result and suggestions on how to reduce the anxiety level in learning second/foreign language.